Anti-tuberculosis Induced Stevens-Johnson Syndrome Due to Misdiagnosis of Mycobacterium Abscessus Urinary Tract Infection as Tuberculosis (Iranian Journal of Kidney Diseases, 2021)
Mycobacterium abscessus complex is one of the most important groups of non-tuberculosis mycobacteria, which can cause infection in several organs of the human body. In this study, we report a rare cause of urinary tract infection which was presented with the chief complaint of hematuria and dysuria. The patient was treated by a clarithromycin based approach and the result of the culture and polymerase chain reaction were negative after 3 months of treatment. Informed consent was taken from the patient for publishing the case.